Union of the Comoros : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Modification of a Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2013)
The Fifth Review under the Extended Credit Facility (ECF) Arrangement for the Union of the Comoros discusses macroeconomic policies and developments of the country. The performance under the ECF-supported program through end-December has been satisfactory. All performance criteria and indicative targets for end-December 2012 have been met, with wide margins in some cases. Macroeconomic developments have been consistent with expectations under the ECF arrangement. IMF staff has proposed modifications to the structural benchmarks, and recommends completion of the fifth review under the ECF arrangement.